TINJAUAN LITERATUR: ETNOFARMASI DAN AKTIVITAS FARMAKOLOGI KULIT PISANG KEPOK (Musa paradisiaca formatypica) - Asman Sadino; Faizah Min Fadhlillah; Dhea Siti Hajar; Riza Apriani (Jurnal Buana Farma, 2026)
Ethnopharmaceutical study is an approach to explore the local knowledge of people from certain tribes and ethnicities regarding the utilization of plants as traditional medicines. This review aims to examine the ethnopharmaceutical utilization and pharmacological activity of kepok banana peel waste (Musa paradisiaca formatypica) based on current scientific evidence. The method used was narrative review through literature searches on Google Scholar and PubMed databases of full-text articles published in the period 2011-2026. The keywords used included “ethnopharmaceutical,” “Musa paradisiaca,” “kepok banana peel”, and “pharmacological activity of Musa paradisiaca.” Included articles were national and international accredited/ISSN publications that addressed the ethnopharmaceutical aspects and pharmacological activity of kepok banana peel, while irrelevant articles and publications below 2011 were excluded. The results showed that kepok banana peel has been utilized as a traditional medicine by several ethnic groups in Indonesia, including Dondo, Kaili, Mori, Sasak, and Banggai. Pharmacologically, kepok banana peel is reported to have several main activities including antidiarrheal, anti-inflammatory, wound healing (cuts and burns), and anti-acne activity. Based on these findings, kepok banana peel waste has the potential to be developed as an ethnopharmaceutical-based traditional medicine ingredient and candidate raw material for pharmaceutical preparations supporting therapy.